2021
DOI: 10.1212/nxg.0000000000000603
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Body Weight on Age at Onset in Huntington Disease

Abstract: ObjectiveWeight loss is associated with clinical progression in Huntington disease (HD), but whether body weight causally affects disease onset or progression is unknown. Therefore, we aimed to assess whether genetically determined variations in body weight are causally related to age at onset in HD.MethodsUsing data from different recent genome-wide association studies, we performed a 2-sample mendelian randomization (MR) analysis to assess whether genetic markers of body mass index (BMI) are causally related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…In addition to prior studies on high caloric diets and the use of transgenic mice to induce weight gain [29-34]; increases in body weight in HD appear to be insufficient to significantly modify disease features in animal models. In line with this, van der Burg and colleagues followed up on results from the original BMI and disease progression study [25] and reported that there is no causal relation between BMI and age of onset in clinical HD [35]. Hence, there is a need for elucidating specific mechanisms underlying HD metabolic changes and how it modifies disease features in HD.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to prior studies on high caloric diets and the use of transgenic mice to induce weight gain [29-34]; increases in body weight in HD appear to be insufficient to significantly modify disease features in animal models. In line with this, van der Burg and colleagues followed up on results from the original BMI and disease progression study [25] and reported that there is no causal relation between BMI and age of onset in clinical HD [35]. Hence, there is a need for elucidating specific mechanisms underlying HD metabolic changes and how it modifies disease features in HD.…”
Section: Introductionmentioning
confidence: 99%
“…However, clinical cases demonstrated that body weight loss is not necessarily the results of the disease itself but rather an insidious consequence of a generally reduced metabolism [ 63 ]. Clinically, HD patients usually suffer from swallowing problems and they are more likely to choke, resulting in lower body mass index than healthy individuals [ 64 ]. In order to assess the aspect of HD-related body weight loss in zQ175 Δneo mice, we also measured the food consumption on a weekly basis.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have demonstrated that the degree of weight loss may correlate with an individual's CAG repeat length, with longer expansions associated with more profound weight loss. 72 Although a person's BMI does not appear to predict age of onset of manifest HD, 73 it may dictate the speed of progression, with lower BMI at disease onset portending more rapid decline in function. 74 The actual cause for weight loss in HD is not entirely understood.…”
Section: Huntington's Diseasementioning
confidence: 99%